2016
DOI: 10.1016/j.cancergen.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelioma families without inheritance of a BAP1 predisposing mutation

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. (n=1), and unknown (n=1). These family units witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…When intense, cytoplasmic staining can obscure the true nature of nuclear signal and lead to interpretation errors. Cytoplasmic staining in MM has been reported up to 27% and explained by sequestration of some mutated BAP1 isoforms in the cytoplasm due to prevented nuclear localisation, resulting in loss of nuclear signal . Some authors have suggested that cytoplasmic BAP1 staining that is together with nuclear negativity could be associated with better prognosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When intense, cytoplasmic staining can obscure the true nature of nuclear signal and lead to interpretation errors. Cytoplasmic staining in MM has been reported up to 27% and explained by sequestration of some mutated BAP1 isoforms in the cytoplasm due to prevented nuclear localisation, resulting in loss of nuclear signal . Some authors have suggested that cytoplasmic BAP1 staining that is together with nuclear negativity could be associated with better prognosis .…”
Section: Discussionmentioning
confidence: 99%
“…21,24 We and most previous studies observed 100% specificity for prevented nuclear localisation, resulting in loss of nuclear signal. 26,27 Some authors have suggested that cytoplasmic BAP1 staining that is together with nuclear negativity could be associated with better prognosis. 26,28 Righi et al 28 showed that 100% of the MM cases with this type of reactivity were mutated, concluding that it is a reliable predictor of BAP1 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons of this finding are not well defined. 19,29,30 One explanation is that somatic alterations in exons coding for nuclear localization signals led to BAP1 protein delocalization. 29 BAP1 cytoplasmic positivity could be used as positive control in cytological samples, when internal control cells are absent.…”
Section: Discussionmentioning
confidence: 99%
“…BAP1 has garnered both research and clinical focus in MPM based on its high rate of mutation, demonstrated role in other malignancies [2], and common use as an immunohistochemical biomarker for MPM diagnosis, particularly for the epithelioid subtype [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The monoclonal antibody C4 (Santa Cruz Biotechnology, Dallas, TX, USA), utilized in most clinical and investigational settings [3,5,[7][8][9][10][11][12][15][16][17][18][19][20][21][22][23][25][26][27], binds within the C-terminal region of the BAP1 protein (aa 430-729). Clinical and research use involves binary evaluation of presence or absence of BAP1 nuclear staining, defined as positive when the nuclei of tumor cells exhibit immunoreactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Most prior investigations utilized small numbers of samples [13][14][15]22,23,25,27,30]. Those including larger numbers have used biopsies [7,10,11,14,17,27], or tissue microarrays [8,12,16,19], including tumor samples insufficient to evaluate potential intra-tumoral heterogeneity of BAP1 staining [9,10,13,23,25]. The objective of the current study was to examine the immunohistochemical localization of BAP1 using clinical blocks from a large cohort of surgically resected MPM cases, of which 263 had BAP1 sequencing data.…”
Section: Introductionmentioning
confidence: 99%